Exploring Strategies to Strengthen the Integrated Inter-Sectoral Collaboration Among Early Childhood Care and Education Providers - Lintle Palesa Jennivieve Manwedi-Thulo; Okeke Chinedu Ifedi; Ugwuanyi Christian Sunday; Akobi Thomas Ogbeche (CV. Literasi Indonesia, 2023)
The study explored strategies that could be used to strengthen the integrated inter-sectoral collaboration among Early Childhood Care and Education (ECCE) providers in the Northern Cape province, South Africa. It is evidenced in the literature that early childhood education centers operate without maximum inter-sectoral collaboration. There is a need therefore for intersectoral collaboration among early childhood providers to ensure a smooth running of the program for children’s development. Semi-structured interviews with a sample of 12 seasoned ECCE providers from the public and private sectors were used to gather the data. Data were analyzed using thematic analysis, and themes were formed. The findings of the study among others indicate that a detailed provincial integrated Early Childhood Care and Education (ECCE) strategy is developed to ensure a properly resourced, coordinated, and managed Early childhood development (ECD) system that forms part of the national ECCE strategy. The study also found that the establishment of a financing model as a strategy can assist to strengthen the integrated inter-sectoral collaboration among ECCE providers.